Charge‐Transfer and Spin‐Flip States: Thriving as Complements. Issue 15 (6th February 2023) - Kitzmann, Winald R.; Heinze, Katja
Abstract: Transition metal complexes with photoactive charge‐transfer excited states are pervasive throughout the literature. In particular, [Ru(bpy)3 ] 2+ (bpy=2, 2′‐bipyridine), with its metal‐to‐ligand charge‐transfer emission, has been established as a key complex. Meanwhile, interest in so‐called spin‐flip metal‐centered states has risen dramatically after the molecular ruby [Cr(ddpd)2 ] 3+ (ddpd= N, N ′‐dimethyl‐ N, N ′‐dipyridin‐2‐yl‐pyridine‐2, 6‐diamine) led to design principles to access strong, long‐lived emission from photostable chromium(III) complexes. This Review contrasts the properties of emissive charge‐transfer and spin‐flip states by using [Ru(bpy)3 ] 2+ and [Cr(ddpd)2 ] 3+ as prototypical examples. We discuss the relevant excited states, the tunability of their energy and lifetimes, and their response to external stimuli. Finally, we identify strengths and weaknesses of charge‐transfer and spin‐flip states in applications such as photocatalysis and circularly polarized luminescence. Abstract : Charge‐transfer excited states have been at the focus of inorganic photochemistry for decades, together with their strongest opponents: detrimental metal‐centered states. In recent years, interest in metal‐centered spin‐flip states was reignited by a new type of photoactive chromium(III) complex. This Review delineates similarities and unique features of charge‐transfer and spin‐flip states, from fundamentals to applications.